O sistema peptídeos natriuréticos está presente no complexo cumulus-oócito e regula o reinício da meiose em bovinos - Cesaro, Matheus Pedrotti de (2013)
The process of meiotic resumption in oocytes, arrested since fetal life, and the expansion of compact layers of cumulus cells is triggered by intrafollicular mediators stimulated by LH. These events are extremely complex. In mice, among system components of natriuretic peptides (NP), only the C-type NP (CNP) has a role to inhibit the resumption of meiosis. However, little is know about the function of NPs on resumption of meiosis, nuclear maturation and cumulus expansion in monovular species. The aim of this study was to characterize the natriuretic peptide system, studing its role in the resumption of meiosis and cumulus expansion. We also proposed a new model to study cumulus expansion. Initially, we detected the presence of mRNA for the ANP, CNP, natriuretic peptide receptor 1 (NPR-1), NPR-2 and NPR-3 in the cumulus cells and NPR-2 mRNA in the oocyte. Using an in vitro model, in which the oocytes are arrested in germinal vesicle (VG) by the action of forskolin (100 μM), we demonstrated that ANP, BNP and CNP, alone or in combination, induce resumption of meiosis after 12 h of maturation. In another experiments, we observed that the concentration of 100 μM forskolin inhibited cumulus expansion stimulated by FSH for12 h, which was reversed by adding ANP, BNP and CNP in the COC culture system. Thus, we demonstrated for the first time the localization of mRNA for the NP system in COCs. Furthermore, we found that the ANP, BNP and CNP are likely mediators of LH to induce meiotic resumption and cumulus expansion in monovuluar species, using the bovine as the animal model.